Sustainable urbanization performance evaluation and benchmarking: An efficiency perspective. Issue 2 (12th March 2018) - Fang, Shuting; Ji, Xiang; Ji, Xinghua; Wu, Jie
Abstract : Purpose: The purpose of this paper is to develop a suitable framework of sustainable urbanization performance evaluation from the view of efficiency for mitigating the unbalance between the theoretical research of sustainable urbanization and the practical need of sustainable urbanization. Design/methodology/approach: A slack-restricted slack-based measure data envelopment analysis (DEA) model and two sustainable urbanization benchmarking methods with individual and centralized view, respectively, are developed based upon the classical DEA theory. Findings: The empirical results show that China is now suffering a relatively low level of sustainable urbanization. Too much waste water emission, too small an urban population proportion, and too much resource wastage are the major factors that drive China's urbanization away from sustainability. Originality/value: Having the overall aim of practical urbanization, the proposed framework can help stakeholders recognize different sustainable urbanization performance levels by offering them accurate sustainable urbanization performance scores. The framework can also direct governments to improve the sustainable urbanization performance. The empirical analysis of China's provincial region sustainable urbanization performance with the proposed framework further demonstrates the theoretical and practical value of this research.